XAP5 CIRCADIAN TIMEKEEPER Affects Both DNA Damage Responses and Immune Signaling in Arabidopsis - Kumimoto, Roderick W.; Ellison, Cory T.; Toruño, Tania Y.; Bak, Aurélie; Zhang, Hongtao; Casteel, Clare L.; Coaker, Gitta; Harmer, Stacey L. (Frontiers in Plant Science, 2021)
Numerous links have been reported between immune response and DNA damage repair pathways in both plants and animals but the precise nature of the relationship between these fundamental processes is not entirely clear. Here, we report that XCT (XAP5 CIRCADIAN TIMEKEEPER), a protein highly conserved across eukaryotes, acts as a negative regulator of immunity in Arabidopsis thaliana and plays a positive role in responses to DNA damaging radiation. We find xct mutants have enhanced resistance to infection by a virulent bacterial pathogen, Pseudomonas syringae pv. tomato DC3000, and are hyper-responsive to the defense-activating hormone salicylic acid (SA) when compared to wild type. Unlike most mutants with constitutive effector-triggered immunity, xct plants do not have increased levels of salicylic acid (SA) and retain enhanced immunity at elevated temperatures. Genetic analysis indicates XCT acts independently of NPR1, which encodes a known SA receptor. Since DNA damage has been reported to potentiate immune responses, we next investigated the DNA damage response in our mutants. We found xct seedlings to be hypersensitive to UV-C and γ radiation and deficient in phosphorylation of the histone variant H2A.X, one of the earliest known responses to DNA damage. These data demonstrate that loss of XCT causes a defect in an early step of the DNA damage response pathway. Together, our data suggest that alterations in DNA damage response pathways may underlie the enhanced immunity seen in xct mutants.